Problems and prospects of using unmanned aerial vehicles in monitoring oil and gas fields - Sibgatullin M. E., Giliazov L. R. (Relevant problems of modern science and education, 2025)
The article examines the problems and prospects of using unmanned aerial vehicles for monitoring oil and gas fields, emphasizing their importance in the context of growing demand for hydrocarbons and stricter environmental standards.
Keywords: Искусственный интеллект; Artificial intelligence; экологическая безопасность; беспилотные летательные аппараты; unmanned aerial vehicles; нефтегазовая отрасль; environmental safety; мониторинг месторождений; field monitoring; oil and gas industry